Interference of Monoclonal Gammopathy with Fibrinogen Assay Producing Spurious Dysfibrinogenemia - Martini, Francesca; Cecconi, Nadia; Paolicchi, Aldo; Galimberti, Sara; Cervetti, Giulia; Buda, Gabriele; Petrini, Mario (TH Open, 2019)
Abnormal coagulation properties indicative of a dysfibrinogenemia were found in the plasma of an asymptomatic 65-year-old male. An immunoglobulin k light chain was found to interfere with Fg functional assay and coagulation tests (activated partial thromboplastin time, prothrombin time, and thrombin time). Steroid therapy reduced the inhibitory effect (after dexamethasone treatment coagulation test and functional Fg value normalized). Spurious dysfibrinogenemia associated with light chain monoclonal gammopathy of undetermined significance was diagnosed.
Keywords: coagulation factors; inhibitor; fibrinogen; fibrin